Pengaruh Lingkungan Pergaulan Teman Sebaya Terhadap Perilaku Cyberbullying pada Generasi Z (Laboratorium Sosiologi FISIP Universitas Jember, 2023)
Advances in Science and Technology (IPTEK) make it easier for us to communicate, find and share information so that interactions occur very easily without the need to meet face to face, namely through social media. However behind this convenience the development of science and technology also has a negative impact where on social media there is the phenomenon of cyberbullying. This phenomenon is a form of bullying behaviour that occurs in social media and not infrequently the perpetrators and victims are peers. In this article, we find out the influence of the peer social environment on cyberbullying behaviour that occurs in generation Z. Using quantitative research methods, and collecting data through questionnaires from the Google form, and also passing a series of tests, namely validity, reliability, normality and linearity tests utilising Microsoft Excel, the results show several findings. The social environment of peers influences 37.1% of cyberbullying behaviour among generation Z while the remaining 62.9% is influenced by other factors such as perpetrators coming from broken homes, wanting to prove themselves and assumptions that perpetrators are better than victims as well as unstable emotions and low emotional control and lack of education.